Determination of exercise intensity domains during upright versus supine cycling: a methodological study - Damir Zubac; Vladimir Ivančev; Vincent Martin; Antonio Dello Iacono; Cécil J.W. Meulenberg; Adam C. McDonnell (PeerJ, 2022)
Background There is a growing interest among the research community and clinical practitioners to investigate cardiopulmonary exercise test (CPET) procedures and protocols utilized in supine cycling. Materials and Methods The current study investigated the effects of posture on indicators of exercise intensity including gas exchange threshold (GET), respiratory compensation point (RCP), and the rate of peak oxygen uptake (V̇O2 peak), as well as the role of V̇O2 mean response time (MRT) in determining exercise intensity domains in nineteen healthy men (age: 22 ± 3 years). Two moderate-intensity step-transitions from 20 to 100 Watt (W) were completed, followed by a maximal CPET. After completing the ramp test, participants performed a constant-load at 90% of their attained peak power output (PPO). Results No differences were observed in the V̇O2 MRT between the two positions, although the phase II-time constant (τV̇O2p) was 7 s slower in supine position compared to upright (p = 0.001). The rate of O2 uptake in the supine position at GET and RCP were lower compared to the upright position (208 ± 200 mL·min−1 (p = 0.007) and 265 ± 235 mL·min−1 (p = 0.012) respectively). Besides, V̇O2 peak was significantly decreased (by 6%, p = 0.002) during supine position. These findings were confirmed by the wide limits of agreement between the measures of V̇O2 in different postures (V̇O2 peak: −341 to 859; constant-load test: −528 to 783; GET: −375 to 789; RCP: −520 to 1021 all in mL·min−1). Conclusion Since an accurate identification of an appropriate power output (PO) from a single-visit CPET remains a matter of debate, especially for supine cycling, we propose that moderate-intensity step-transitions preceding a ramp CPET could be a viable addition to ensure appropriate exercise-intensity domain determination, in particular upon GET-based prescription.